2012
DOI: 10.1253/circj.cj-12-0662
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Rho-Kinase Activation in the Pathogenesis of Coronary Hyperconstricting Responses Induced by Drug-Eluting Stents in Patients With Coronary Artery Disease

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp are-metal stents (BMS) and, more recently, drug-eluting stents (DES), such as sirolimus-eluting (Cypher TM ) and paclitaxel-eluting stents (Taxus TM ), have further improved early results and reduced the risk of restenosis. 1,2 However, DES have also not been shown to improve longterm survival of patients with coronary artery disease (CAD) compared with BMS. 3 Moreover, there is a concern on the safety issues of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…288,289 Recent studies in a porcine model and in patients with coronary artery disease have suggested that Rho-kinase, a molecular switch that regulates vascular smooth muscle contraction, plays an important role in the pathogenesis of coronary dysfunction after DES implantation, and that DES induces smooth muscle dysfunction as well as endothelial dysfunction. 290, 291 These findings suggest that vascular dysfunction following DES implantation is an important target for clinical intervention.…”
Section: Coronary Spasm After Pcimentioning
confidence: 99%
“…288,289 Recent studies in a porcine model and in patients with coronary artery disease have suggested that Rho-kinase, a molecular switch that regulates vascular smooth muscle contraction, plays an important role in the pathogenesis of coronary dysfunction after DES implantation, and that DES induces smooth muscle dysfunction as well as endothelial dysfunction. 290, 291 These findings suggest that vascular dysfunction following DES implantation is an important target for clinical intervention.…”
Section: Coronary Spasm After Pcimentioning
confidence: 99%
“…15, 16 Quantitative coronary angiography (QCA) (INFX-8000V; Toshiba Medical Co, Tokyo, Japan) was performed in a blind manner at the proximal and distal stent edge segments adjacent to the stent (5 mm apart from the proximal and distal stent end portions), as previously described. 5 animals and humans, 8,13, 14 and that it also plays a key role in the pathogenesis of coronary hyperconstricting responses after the first-generation DES implantation in animals 15, 16 and humans 5 as compared with the bare-metal stents. Nevertheless, it remains to be elucidated why DES-induced coronary hyperconstriction spontaneously develops at the proximal and distal stent edges.…”
Section: In Vivo Assessment Of Coronary Vasomotionmentioning
confidence: 99%
“…However, the authors performed OCT imaging analysis to provide detailed information on the intimal area of the coronary artery. 7 The results demonstrated a lack of correlation between intimal hyperplasia and DES-induced coronary hyperconstrictive response. This result is consistent with the previous finding that coronary vasospasm is associated with a variable degree of intimal hyperplasia in a swine model of coronary vasospasm.…”
Section: Article P 2552mentioning
confidence: 92%